Adverse events and potentially preventable deaths in Dutch hospitals: results of a retrospective patient record review study. Issue 4 (3rd August 2009) - Zegers, M; de Bruijne, M C; Wagner, C; Hoonhout, L H F; Waaijman, R; Smits, M; Hout, F A G; Zwaan, L; Christiaans-Dingelhoff, I; Timmermans, D R M; Groenewegen, P P; van der Wal, G
Abstract : Objective: This study determined the incidence, type, nature, preventability and impact of adverse events (AEs) among hospitalised patients and potentially preventable deaths in Dutch hospitals. Methods: Using a three-stage retrospective record review process, trained nurses and doctors reviewed 7926 admissions: 3983 admissions of deceased hospital patients and 3943 admissions of discharged patients in 2004, in a random sample of 21 hospitals in the Netherlands (4 university, 6 tertiary teaching and 11 general hospitals). A large sample of deceased patients was included to determine the occurrence of potentially preventable deaths in hospitals more precisely. Results: One or more AEs were found in 5.7% (95% CI 5.1% to 6.4%) of all admissions and a preventable AE in 2.3% (95% CI 1.9% to 2.7%). Of all AEs, 12.8% resulted in permanent disability or contributed to death. The proportion of AEs and their impact increased with age. More than 50% of the AEs were related to surgical procedures. Among deceased hospital patients, 10.7% (95% CI 9.8% to 11.7%) had experienced an AE. Preventable AEs that contributed to death occurred in 4.1% (95% CI 3.5% to 4.8%) of all hospital deaths. Extrapolating to a national level, between 1482 and 2032 potentially preventable deaths occurred in Dutch hospitals in 2004. Conclusions: The incidence of AEs, preventable AEs and potentially preventable deaths in the Netherlands is substantial and needs to be reduced. Patient safety efforts should focus on surgical procedures and older patients.